Characterization of temperature-dependent echo-shifts and backscattered energy induced by thermal ultrasound - Ruano, M. Graça (2013)
Existence of accurate temporal-spatial temperature models, which would enable non-invasive estimates, will promote ultrasound-based thermal therapy applications. These models should reflect the tissue temperature with a maximum absolute error of 0.5 ºC within 1 cm3. In-vitro experiments have been developed to evaluate the temperature variations induced by standard ultrasound therapeutic device emitting continuously on gel-based phantom and on pork meat tissue using three different emitting intensities (1, 1.5 and 2 W/cm3). Temperature estimates were performed based on raw RF data collected using a second ultrasound transducer (imaging transducer). This second transducer worked in pulse-echo mode, and was placed perpendicularly to the therapeutic transducer. In order to access the quality of the estimates, temperatures were acquired by five and by two thermocouples placed in the gel-based phantom and on the porcine sample, respectively. At every 10 seconds the temperature and one RF-line is stored in a PC for future processing. The possibility to estimate temperature was assessed by considering two RFline features: temporal echo-shifts produced by changes in speed-of-sound and medium expansion/contraction and by changes on the backscattered energy originated by medium inhomogeneities. On one hand, results prove that echo-shifts correlated with temperature in both types of medium (phantom and ex-vivo porcine muscle). On the other hand, analyzing the backscattered energies one may conclude that this measures correlates with temperature in the porcine sample and not on the phantom. This led us to conclude that the developed phantom is not appropriate for studying changes on backscattered energy with temperature. Energy analysis of the porcine sample confirms the non-uniform temperature variation due to the existence of a heterogeneous media with different sound propagation velocities.